Factors Associated With Physical Activity and Sedentary Behavior in People With Parkinson Disease: A Systematic Review and Meta-Analysis - Domingues, Vitoria L.; Makhoul, Marina P.; de Freitas, Tatiana B.; Polese, Janaine C.; Silva-Batista, Carla; Barbieri, Fabio A. [UNESP]; Torriani-Pasin, Camila (Oxford University Press (OUP), 2024)
Objective. The goal of this review was to investigate factors associated with physical activity and sedentary behavior in people with Parkinson disease (PD). The magnitude of these associations was investigated in line with the International Classification of Functioning, Disability and Health components. Methods. A systematic literature review was conducted until February 2023, searching four databases (PubMed, EMBASE, Web of Science, and Scopus) for original articles investigating associations with physical activity or sedentary behavior in people with PD. Two independent researchers performed data extraction, and the risk of bias in the included studies was assessed using the Quality in Prognosis Studies tool. Meta-analyses were conducted to determine the magnitude of the associations, and significant regression models from the included studies were described. Results. Forty-two studies were included. Twenty-one factors associated with overall physical activity were identified. Higher levels of physical activity had a small association with cognition and body mass index and a fair association with 17 factors related to self-efficacy, physical function, mobility, quality of life, age, PD symptoms, and more. Better manual dexterity and functional gait had moderate to good associations with higher levels of physical activity. The regression model with the higher magnitude was composed mostly of contextual factors, except for the body max index. The magnitude of factors associated with physical activity intensity or sedentary behavior could not be identified. Conclusion. Functional gait and manual dexterity were the strongest factors related to physical activity in people with PD. Further investigation is needed to understand the factors associated with physical activity intensity and sedentary behavior. Impact. This study emphasizes the significance of considering contextual factors alongside body function and structure, activity and participation, and the health condition to enhance physical activity improvement during the rehabilitation process. By adopting such a holistic approach, rehabilitation professionals can optimize the overall health and well-being of individuals with Parkinson disease
Keywords: Active Lifestyle; Exercise; Inactive Lifestyle; Motor Symptoms; Rehabilitation